"Baba Has Come to Civilize Us": Developmental Idealism and Framing the Strict Demands of the Brahma Kumaris. Issue 4 (1st February 2017) - McKendry‐Smith, Emily
Abstract : This article extends and complicates the theory that "strict churches are strong" based on the strict demands that were followed and not followed by the Brahma Kumaris in Nepal. To be successful, strict religious groups must not only be strict, but also frame their strictness in ways that resonate with the everyday experiences and commonly held beliefs of their members. Nepali women involved with the Brahma Kumaris tend to accept and follow the group's demands when those demands have been framed as modern, and that framing is resonant with the prevailing definitions of modernity offered by Western development agencies. When the modern framing is not resonant, as with the case of framing celibacy as "spiritual birth control, " the strict demand is not followed, and the frame itself is rejected in favor of the practice being defined in different terms.